Optical Fiber Microsensor of Semidrop - Molina-Flores, Esteban; López-Flores, R. B.; Molina-Flores, Daniel; Dávila-Píntle, José A.; Gracios-Marín, Germán A. Muñoz-Hernández Carlos A.; Morales-Rodríguez, Enrique (IntechOpen, 2011)
None